In vivo method to evaluate antioxidative activity using UVA‐induced carbonylated protein on human skin. (12th June 2021) - Cho, Changhui; Lee, Eunyoung; Cho, Eunbyul; Yoo, Heejoo; Bae, Jiyoun; Ha, Jaehyoun; Hwang, Jaesung
Abstract: Background: Skin is continuously exposed to oxidative stress caused by reactive oxygen species (ROS) produced by the ultraviolet (UV) light, and it is important to evaluate the antioxidant activity. Carbonylated proteins (CPs) are candidate markers of oxidative modification as a result from the ROS. We aimed to develop the CP‐based method to assess the efficacy of antioxidants in human skin. Methods: Ten healthy females were enrolled in the study to determine the UVA dosage for CP production, and another 10 females were included to evaluate the antioxidative activity. The stratum corneum was collected from test skin using D‐Squame tape, and CPs from the SC were stained by fluorescence labeling and observed using a fluorescence microscope. Results: CP level significantly increased with UVA irradiation from 15J/cm 2 to 50J/cm 2 compared to the control (non‐UVA) area. CP production significantly increased by 34.38% and 35.22% in UVA irradiation and squalene (vehicle) areas. 5% α‐tocopherol and β‐carotene significantly increased the CP production by 20.77% and 19.34% after 2 hours of 30J of UVA irradiation compared to control area. Inhibition rate of CPs in 5% α‐tocopherol and 5% β‐carotene showed 41.45% and 45.37% after 2 hours of UVA irradiation. Conclusion: This study developed the simple, visual, and direct in vivo method to evaluate the antioxidative activity for products in human skin by measuring the CP level as an oxidative modification caused by UVA‐induced ROS generation.